Ethnomycological studies on some macro-fungi in Rupandehi District, Nepal - Aryal, HP; Budathoki, U (Banko Janakari, 2013)
This ethnomycological investigation explores the wild edible microfungi with their identification and documentation of nutritional potential and indigenous knowledge. The study area occupies 154.75 hectare-land, and lies within a narrow limit of altitude between 110 m and 165 m above sea level in tropical deciduous riverine forest. Amanita caesarea, A. chepangiana, A. pantherina, Agaricus augustus, Coprinus comatus, C. plicatilis, Macrolepiota fuliginosa, M. rhacodes, Russula emetica, R. foetens, R. nigricans, Scleroderma bovista, S. citrinum, Termitomyces clypeatus and T. eurhizeus are found to be dominant. The collected samples represented 27 species of Basidiomycetes belonging to 6 orders, 13 families and 18 genera. The dried specimens are housed in the Tribhuvan University Central Herbarium, Kirtipur, Kathmandu, Nepal. The area embraces many mycophagous ethnic communities. The mycoelements prevailing in this area need sustainable conservation and utilization. Banko Janakari, Vol. 23, No. 1, Page 51-56 DOI: http://dx.doi.org/10.3126/banko.v23i1.9467